Formability of Magnesium AZ80 - Soomro, Muhammad Waseem (Auckland University of Technology, 2016)
Economical and fuel-efficient vehicles are a current topic of interest worldwide, due to increasing fuel costs and environmental concerns. The most strident demand from various auto-sector stakeholders is to reduce emissions from vehicles and keep the environment clean. To solve this issue we need to reduce vehicle weight to lower fuel consumption. In this context, magnesium alloys can be considered as an alternative for sheet metal components, as they are 35 percent lighter than aluminium alloys and 78 percent lighter than steel. The AZ magnesium alloy series is widely used by the modern light metal industry. In this research, AZ80 magnesium alloy was selected. AZ80 is an important structural wrought-magnesium alloy with a high aluminium content of about 8 wt. %. AZ80 is the main subject of this study because it offers higher strength and greater hardness than the more widely used AZ31. In this research, magnesium AZ80 alloys with two different grain sizes were considered, that is fine grain AZ80 (grain size ≈ 10 µm) and coarse grain AZ80 (grain size ≈ 60 µm). These grain sizes were chosen for investigations of the effect of grain size at higher temperatures and to observe changes in mechanical and forming capabilities with respect to grain size. To investigate the formability characteristics of magnesium alloys, various tensile tests and deep drawing tests were performed at different temperatures, test speeds and grain sizes to understand the nature of the material. Anisotropy of material, strain sensitivity index and flow stress were also determined by varying all of these parameters. Moreover, load-displacement diagrams, forming-limit diagrams and the effects of variations in various pre-and-post processing parameters were also examined. A further part of this research was to examine microstructure changes through the use of microscopic images at high magnification by utilising optical and scanning electron microscopes. It was observed that the microstructure of magnesium alloys was extremely sensitive to processing parameters in tensile tests and deep-drawing tests. The final part of the research was the verification of mathematical modelling and simulation of metal forming processes by using the commercial FEA software package Abaqus.
Keywords: Magnesium; Formability; Light weight; Microstructure